Magnetophoretic Migration Of Magnetic Nanoparticles Through Cellulose Matrix - Mohd Salleh, Muhammad Sufian (Universiti Sains Malaysia, 2021)
The migration of magnetic nanoparticles (MNPs) through cellulose matrix has been presented in this thesis. The experiment was carried out to study the influence of colloidal stability, aggregation of MNPs, concentration, the pore size of the cellulose matrix, and strength of magnetic field on the magnetophoresis of MNPs through the complex structure of cellulose. Magnetite, Fe3O4 were used as the MNPs to study the magnetophoresis under an Optical microscope. All the captured images of the magnetophoretic phenomena were analysed by using NIH ImageJ. A simple setup of the experiment was done by placing a magnet 2 cm away from the initial point of MNPs was injected on the Whatman chromatography paper. Based on the experiments conducted, 100 mg/L of poly (sodium (4) styrene sulfonate) polyelectrolyte (PSS) coated MNPs were able to migrate through grade 4 paper after 30 and 60 s of magnetophoresis with 0.007492 % and 0.0162 % of the area covered at 2 cm, respectively. As for naked MNPs with the same conditions, the area covered after 30 and 60 s is 0 and 0.00133 % respectively. It was found that the area covered for the magnetophoretic motion of MNPsthrough grade 5 paper was lower than grade 4 paper, whereas at 1.5 and 2 cm the area covered is 0.00245 % and 0.00294 % respectively. Besides, a higher concentration of MNPs solution will limit the magnetophoresis of MNPs through the matrix due to the formation of aggregation that inhibits the motion of the particles from passing through the pore of the cellulose matrix.